Enhancing surgical precision and efficiency: a study and comparison of a three-dimensional surgical video system in proliferative diabetic retinopathy surgery - Zhang, Xiang; Zhu, Danni; Li, Wenbo; Hu, Hanling; Nie, Zetong; Guo, Haoxin; Wang, Zhaoxiong; Li, Xiaorong; Hu, Bojie (Frontiers in Medicine, 2023)
Purpose This study aimed to investigate the safety and efficacy of three-dimensional (3D) surgical video systems for proliferative diabetic retinopathy (PDR). Methods This retrospective clinical case study included 30 patients (30 eyes) with PDR. Patients were divided into two groups: one underwent surgery using a 3D surgical video system (14 cases, 14 eyes), while the other underwent traditional microscope surgery (16 cases, 16 eyes). Safety and efficacy were assessed through predetermined surgical parameters, including surgical duration, intraoperative membrane removal rate, and occurrences during intraoperative and postoperative phases. Results Our study revealed noteworthy differences in various aspects between the 3D surgical video system group and the traditional microscope surgery group. Specifically, the mean surgical time was 30.25 ± 14.43 mins in the 3D surgical video system group, while it was 38.56 ± 18.71 mins in the traditional microscope surgery group (p = 0.051). Furthermore, the mean membrane removal time was significantly shorter in the 3D group at 2.53 ± 1.52 mins, as compared to 3.23 ± 1.76 mins in the traditional group (p = 0.042). Importantly, the membrane removal rate also displayed a significant difference, with the 3D group at 0.55 ± 0.07 and the traditional group at 0.41 ± 0.11 (p = 0.018). However, no notable differences were observed between the two groups in terms of intraoperative and postoperative incidences. Conclusion The safety and efficacy obtained using the 3D surgical video system in PDR surgery were comparable to those obtained in traditional microscopic surgery.